Testing for Testamentary Capacity in the Older Adult: A Model of Ethical Considerations for the Clinical Neuropsychologist - Roche, Anne I. (Frontiers in Psychology, 2019)
The proportion of the United States population comprised of older adults is consistently growing. Older adults are often involved in making decisions regarding transfer of wealth, and cases involving questions of testamentary capacity are common. Neuropsychologists are well-positioned to perform evaluations of testamentary capacity given their knowledge and expertise surrounding assessment of cognitive and psychological functioning, as well as of neurodegenerative disease related to the aging process. Performing evaluations of testamentary capacity with older adults often comes with complex ethical considerations, however, and neuropsychologists could benefit from a decision-making model to aid in the organization of these multifaceted issues at the clinical-legal interface. The current paper proposes the implementation of Behnke’s “four bin” model to aid in the exploration of these complex ethical considerations and provides examples of how the model may be applied through two hypothetical case vignettes.